Culturing the fruits of the forest: realising the multifunctional potential of space and place in the context of woodland and/or Forest Schools - Morgan, Alun (Journal of Outdoor and Environmental Education, 2018)
This paper seeks to explore the potential of woodland as a milieu for Outdoor and Environmental Learning (OEL) in the context of phenomenal rise of Forest Schools (FS) in the United Kingdom. Whilst broadly supportive of these developments, the paper adopts a critical stance in arguing that the notion of the ‘forest’ as a literal and metaphoric wild and expansive space of risk, excitement, freedom, exploration and intimate contact with nature which underpins the original FS concept seems to be giving way to a diluted sense of controlled spaces and activities for curriculum enrichment, a process referred to as ‘scolonisation’. Furthermore, the paper considers FS in relation to two ‘axes’: ‘learning milieu’ and ‘practitioners’, arguing that a spectrum exists from, on the one hand, relatively ‘deforested’ to substantially wooded learning contexts; and, on the other, novice through to expert practitioners. The paper argues that the most efficacious woodland-oriented Outdoor Learning will take place in woodland environments under the facilitation of ‘silvanatives’ – those with substantial practical and pedagogical knowledge about learning in woodland contexts. However, this ideal potential is under-realised when the learning context is relatively ‘deforested’, or practitioners are relatively ‘silvanaïve’ or superficially trained, trends that are seemingly increasingly characterising the movement as it becomes ‘scaled-up’.